PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PRESTASI BELAJAR SISWA DI SMK TRITECH MEDAN - Indra Wahyudi Z; Indah Mayasari; Lia Sumayyah (Cemara Education and Science, 2025)
This study aims to analyze the effect of using interactive learning media on student learning achievement at SMK Tritech Medan. Interactive learning media is a tool designed to increase interaction between students and subject matter, so that it is expected to improve student learning outcomes. The research method used is experimental method with quantitative approach. Students who used interactive learning media showed a higher increase in learning achievement compared to students who used conventional learning media. In addition, students also showed a more positive attitude towards the learning process, which was characterized by increased active participation, enthusiasm, and learning satisfaction.